Electrical properties of Se80-xTe20Sbx (0 ≤ x ≤ 12) nanorods. (17th August 2018) - Deepika,; Singh, Hukum
Abstract: The present study reports the electrical properties of Se80−x Te20 Sbx (0 ≤ x ≤ 12) nanorods as a function of temperature and composition. The amorphous bulk powder of Se80−x Te20 Sbx (0 ≤ x ≤ 12) glasses were prepared using melt quenching method and the nanostructured thin films were prepared using physical vapor condensation method. These thin films were characterized using XRD, SEM and TEM. TEM images indicate the formation of nanorods within the thin film samples. I–V measurements were carried out in temperature range 303–373 K and electrical conductivity of nanostructured Se80−x Te20 Sbx (0 ≤ x ≤ 12) thin films was determined. Two conduction mechanisms were observed in the Se80−x Te20 Sbx (0 ≤ x ≤ 12) nanostructured system. In higher temperature range (343–373 K), conduction takes place through thermally assisted tunnelling of charge carriers while in the temperature range 303–343 K, variable range hopping of charge carriers contributes to conduction. VRH was also tested for lower temperature (263–303 K) range for SeTeSb3 sample and was found to be the conduction mechanism at lower temperatures also.